STUDY OF CONCRETE FRACTURE SLl\iULA T!ON USING ANSYS - Awi, Azree Azhar (Universiti Teknologi Petronas, 2008)
Major probl~m in concret~ is rracture dlle to excess load acting on it or failure due to tension or shear. This project focused orl the computer simulation of concrete fracture using ANSYS software. Though, ANSYS software helps simulate the cracking and concrete fracture simulatiorl in calculating the most important stress intensity factor using in-built crack analysis engine. Using several perimeters and different type of load, several types of fracture will be getting. A concrete fracture model is analyzed to find the precise results in order to simulate through this project. Finite-element Method is being used in this studies and Linear Elastic Fracture Model is recognized to be the most efficient lTJcture model to be used in ANSYS. This study of silhulatlort wnf be beneficlal to all in a way to have better understanding of concrete fhidute occurrence !ilitl this is imporhlht in big construction companies which use concrete as their core matetial consttllctlbh ..